AUTHORSHIP OF THE JAWI ‘ULAMA’ IN EGYPT - Jajang A Rohmana (Sayyid Ali Rahmatullah Tulungagung State Islamic University, 2020)
Nawawī of Banten (1813–1897) and Haji Hasan Mustapa (1852–1930) are two important figures of Malay-Indonesian Muslim scholars (‘ulamā’) who have been widely studied. However, personal proximity of these two ‘ulamā’ seems to escape from scholarly discussion. Seen from the light of scholarly commenting (sharh) tradition, this study on the other hand attempts to show their personal proximity between the senior teacher and young student when they lived in Mecca in the late nineteenth century. The sharh tradition of these two ‘ulamā’ particularly through appear in Nawawī’s al-’Iqd al-Thamīn that aims to comment on Mustapa’s work, Al-Fath al-Mubīn, and Mustapa’s al-Lum’a al-Nūrāniyya, a response to Nawawī’s al-Shadra al-Jummāniyya. These two Arabic books (s. kitab; p. kutub) were published in Cairo, Egypt. This article further argues that the sharh tradition situates authority and reputation as the epicenter of scholarly discussion between the two ‘ulamā’ who were influential among the Jawah community. It also argues that these two Sundanese scholars contributed significantly in the transmission of Islamic learning in the early twentieth century Middle East. Their works show a scholarly reputation which delivers insights on exceptionality of Islamic and Malay archipelagic issues and serve as a global contribution of Malay-Indonesian ‘ulamā’ to the triumph of Islamic learning traditions.